Time‐dependent diffusivity and kurtosis in phantoms and patients with head and neck cancer. Issue 2 (11th October 2022) - Solomon, Eddy; Lemberskiy, Gregory; Baete, Steven; Hu, Kenneth; Malyarenko, Dariya; Swanson, Scott; Shukla‐Dave, Amita; Russek, Stephen E.; Zan, Elcin; Kim, Sungheon Gene
Abstract : Purpose: To assess the reliability of measuring diffusivity, diffusional kurtosis, and cellular‐interstitial water exchange time with long diffusion times (100–800 ms) using stimulated‐echo DWI. Methods: Time‐dependent diffusion MRI was tested on two well‐established diffusion phantoms and in 5 patients with head and neck cancer. Measurements were conducted using an in‐house diffusion‐weighted STEAM‐EPI pulse sequence with multiple diffusion times at a fixed TE on three scanners. We used the weighted linear least‐squares fit method to estimate time‐dependent diffusivity, D ( t ) D(t) , and diffusional kurtosis, K ( t ) K(t) . Additionally, the Kärger model was used to estimate cellular‐interstitial water exchange time ( τ ex τ_ex ) from K ( t ) K(t) . Results: Diffusivity measured by time‐dependent STEAM‐EPI measurements and commercial SE‐EPI showed comparable results with R 2 above 0.98 and overall 5.4 ± 3.0% deviation across diffusion times. Diffusional kurtosis phantom data showed expected patterns: constant D D and K K = 0 for negative controls and slow varying D D and K K for samples made of nanoscopic vesicles. Time‐dependent diffusion MRI in patients with head and neck cancer found that the Kärger model could be considered valid in 72% ± 23% of the voxels in the metastatic lymph nodes. The median cellular‐interstitial water exchange time estimated for lesions was between 58.5 ms and 70.6 ms. Conclusions: Based on two well‐established diffusion phantoms, we found that time‐dependent diffusion MRI measurements can provide stable diffusion and kurtosis values over a wide range of diffusion times and across multiple MRI systems. Moreover, estimation of cellular‐interstitial water exchange time can be achieved using the Kärger model for the metastatic lymph nodes in patients with head and neck cancer.